2017
DOI: 10.1016/j.stemcr.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell-Derived Cardiomyocyte Encapsulating Bioactive Hydrogels Improve Rat Heart Function Post Myocardial Infarction

Abstract: SummaryTissue engineering offers an exciting possibility for cardiac repair post myocardial infarction. We assessed the effects of combined polyethylene glycol hydrogel (PEG), human induced pluripotent stem cell-derived cardiomyocyte (iPSC-CM), and erythropoietin (EPO) therapy in a rat model of myocardial infarction. PEG with/out iPSC-CMs and EPO; iPSC-CMs in saline; or saline alone was injected into infarcted hearts shortly after infarction. Injection of almost any combination of the therapeutics limited acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 39 publications
2
96
0
Order By: Relevance
“…In addition, the treatment efficacy and the survival of iPSC-CMs in vivo after transplantation is debatable. Chow et al demonstrated that no grafted iPSC-CMs were detected after 1 month of transplantation [22]. In the present study, we aimed to evaluate the ability of human iPSC-CM transplantation to improve myocardial function in the rat MI model and to determine the fate of transplanted cells in the rat heart.…”
Section: (Continued From Previous Page)mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the treatment efficacy and the survival of iPSC-CMs in vivo after transplantation is debatable. Chow et al demonstrated that no grafted iPSC-CMs were detected after 1 month of transplantation [22]. In the present study, we aimed to evaluate the ability of human iPSC-CM transplantation to improve myocardial function in the rat MI model and to determine the fate of transplanted cells in the rat heart.…”
Section: (Continued From Previous Page)mentioning
confidence: 91%
“…Human iPSC-CMs have great potential in disease treatment because they avoid the social ethical issues of ESCs and avoid the possibility of immune rejection [20]. Although some investigators reported that transplantation of iPSC-CMs reduced remodeling of the heart after ischemic damage [21][22][23][24], the field is still at the preclinical stage due to technical and surgical hurdles. In addition, the treatment efficacy and the survival of iPSC-CMs in vivo after transplantation is debatable.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…However, improvements have been made in generating mature iPSC-derived cardiomyocytes with high purity and sufficient numbers, and these improvements are expected to enhance the cell retention rate by increasing the number of transplanted cells and to reduce the risk of tumorigenesis and arrhythmia associated with undifferentiated immature cells 77,78 . In addition, providing scaffolds for iPSC-derived cardiomyocytes, such as hydrogels or cell sheets, has been shown to improve therapeutic outcomes 79,80 . Regardless of the advancement in transplantation methods, before translating these therapies to clinical trials, studies in large-animal models are warranted to assess the efficacy and safety of iPSC-derived cardiomyocyte-based therapy.…”
Section: Cell-based Therapies For Cardiac Repairmentioning
confidence: 99%
“…To address this issue, biomaterials have attracted attention for their capacity to serve as a matrix to improve graft survival and behaviour, as well as to protect the therapeutic factors from degradation and to act as a reservoir for sustained local delivery of therapeutic factors. Biomaterial-based delivery systems thus provide a scaffold to improve the therapeutic effects of both cellular and noncellular approaches 79,102,195197 . Furthermore, tissue-engineering technologies have allowed the building of myocardial patches and sheets and 3D heart tissues recapitulating in vitro the complex structure of heart tissue.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The gelation of PEG solution occurred after it came into contact with the physiological environment, and the hydrogel degradation was inversely proportional to the polymer concentration. The injection of the hydrogel containing both human‐induced pluripotent stem cells and erythropoietin into infarcted murine muscle led to the formation of cardiac tissue over 10 weeks of treatment (Chow et al, ).…”
Section: Hydrogels For Treatment Of Diabetes‐related Conditionsmentioning
confidence: 99%